Gamification and mHealth technology: an approach to raise awareness and provide health education to the elderly - Martins, Levi M.; Sousa, Renata J. G.; Moreira, Evaldinolia G.; Conceição, Dário V.; Ferreira, Jeane S. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2017)
According to the World Health Organization 31% of the deaths worldwide are caused by Cardiovascular Diseases (CVDs) and most are preventable by changing risk behaviors. It is known that aged people are more susceptible to have chronic diseases, and that the number of elderly is increasing. At the same time, the concern of public health systems on how to deal with this fact is emerging. The use of gamification is still not much explored when focused on aged people and represents a different approach to motivate and engage the target people in beneficial activities and teach them about a healthy lifestyle. In this paper we propose the use of an app with the adoption of gamification techniques, as a tool to provide medical literacy, prevention and behavioral changes.